Kinerja dan Kesulitan Keuangan Perusahaan dengan Keberagaman Gender sebagai Variabel Moderasi antara - Ariyanto, Stefanus; Effendi, Della (Universitas Multimedia Nusantara, 2025)
The purpose of this study is to collect empirical data on the influence of board gender diversity on the relationship between company performance and governance, and its impact on financial distress. Secondary data from the Indonesian Stock Exchange (IDX) annual financial reports of industrial enterprises for the period of 2019 to 2022 were analyzed. Thirty manufacturing enterprises met the requirements after the sample was selected through purposive sampling. The analysis of the data was done by multiple linear regression. The results show that institutional ownership and gender diversity on the board have no discernible impact on financial distress, while liquidity and leverage taken separately have a negative impact. Nonetheless, when considered collectively, institutional ownership, gender diversity on the board, liquidity, and leverage all have an impact on financial distress; in fact, gender diversity on the board can reinforce and magnify the effects of liquidity and leverage. This study contributes to the theoretical development of the Modified Altman Z-Score by incorporating gender as a moderating variable. The findings imply that gender effects should be considered when assessing a firm’s likelihood of experiencing financial distress. Keywords: Altman Z-Score; Financial Distress; firm performance; Gender Diversity